A tubular luminescent framework: precise decoding of nitroaniline isomers and quantitative detection of traces of benzaldehyde in benzyl alcohol. Issue 29 (18th May 2020) - Wu, Dong; Zhou, Kang; Tian, Jiayue; Liu, Caiping; Jiang, Feilong; Yuan, Daqiang; Chen, Qihui; Hong, Maochun
Abstract : A novel luminescent framework that could be used to precisely identify nitroaniline isomers and quantitatively detect traces of benzaldehyde in benzyl alcohol was reported. Abstract : Precise identification of each isomer among a series of isomers remains a formidable challenge. Herein, a novel luminescent framework (FJI-H26 ) with 1.6 nm nanochannels was prepared. It was used to precisely decode o -nitroaniline, m -nitroaniline, and p -nitroaniline, because of the specific matching between the emission spectrum of FJI-H26 and the absorption spectrum of every nitroaniline isomer. Furthermore, it was used to quantitatively detect traces of benzaldehyde from benzyl alcohol injections, and its linear ranges completely conformed to the requirements of both Chinese and European Pharmacopoeias. Such decoding behavior based on discriminative matching between the emission spectrum of a chemosensor and the absorption spectra of analytes has not been reported so far, and this can prove to be a potential strategy for the development of new chemosensors for precisely decoding isomers.